Letting AV Media Work for You - Jarvis Stoddart (The Canadian Network for Innovation in Education (CNIE), 1989)
Over the years, a great deal of research has been devoted to the study of the cost effectiveness of media. This article is an attempt to summarize some of the research as found in the books and articles listed in the references.